Timing and Shoot Section Influence Success of Tea- Cutting Propagation in a Temperate Climate - Srijana Shrestha; Carol Miles (Horticulturae, 2025)
Tea (Camellia sinensis) is the second most popular beverage in the United States (water is the first), but there is essentially no commercial production due to limited knowledge regarding cultivars and propagation. The objective of this study was to determine the best time of year to collect tea cuttings, the section of the shoot to collect cuttings, and the number of nodes per cutting for successful propagation while optimizing resource efficiency. To address this objective, two experiments were conducted in western Washington, USA, using cv. Minto Pacific. The first experiment (Expt. 1) evaluated the time of year (September through February) for cutting collection and the role of shoot section on successful propagation. The second experiment (Expt. 2) tested one-, two-, and three-node cuttings on the success rate of propagation. In Expt. 1, 5 months after the cutting collection, the survival of tea cuttings collected from late September through early February was 97% in year 1 and 86% in year 2. Survival was similar for all the shoot sections 5 months after collection in year 1 (94%), and in year 2, the top shoot section had the greatest survival (93%). Overall, the plant height, number of new leaves, plant health rating, root number, and root length in the summer following collection were greatest for cuttings collected in early September through late October. Also, overall, the mid-section of the shoot had the greatest plant height, number of new leaves, plant health rating, and root length the summer following collection. In Expt. 2, the survival of all the cuttings was 100% in year 1 and 87% in year 2 at 5 months after cutting collection. The plant height, root number and root length the summer after collection were similar for all the treatments in both years. The results from these two experiments indicate late October may be the optimum time for tea-cutting collection in this temperate climate region, to optimize use of greenhouse facilities, and single-node cuttings maximize the number of cuttings without a reduction in size of the rooted plants.